Recent Land Use Changes on an Urban Watershed in Moncton, New Brunswick, Canada - LeBlanc, Mélanie; Fortin, Guillaume (Environnement urbain / Urban Environment)

(untitled) (Institut National de Recherche Scientifique Centre Urbanisation Culture et Société, 2015)
Changes in land use, which threaten ecosystems and habitats, have an impact on run-off and water quality on urban areas. Using a GIS program we have classified the land use of the Humphreys Brook watershed and quantified the changes that have occurred using landscape metrics. A rapid growth of the city emerges from our results. All land use types of urban nature have seen an increase in surface areas to the detriment of natural land uses. Moreover the landscape indices are showing signs of rectangularity, where humans have introduced straight edges, and other common processes of transformation to the landscape.